Exploring the utility of the 3-minute all-out running test in assessing match performance and external loads in university soccer players - Duncan Peter Sutcliffe; Mark Kramer (PLoS ONE, 2025)
Purpose This study evaluated the utility of the 3-minute all-out running test (3MT) in assessing match performance and physiologically relevant load metrics among male university soccer players. We aimed to explore the relationship between 3MT metrics, including critical speed (CS), finite energy reserve (D’), and maximal running speed (Smax), with key match performance indicators, while also assessing the efficacy of a modified method for tracking player load. Methods Twenty-six male university soccer players completed the 3MT to determine CS, D’, and maximal speed (Smax). Match performance data (n = 3–8 matches per player) were concurrently gathered, including total distance covered, high-speed running (HSR), very high-speed running (VHSR), and overall player load. Correlation analyses were conducted to examine the relationships between 3MT variables and match performance, with a specific focus on how a modified load-tracking method compared to traditional approaches. Results Players with higher CS exhibited smaller fluctuations in D’ kinetics, indicating more efficient energy utilization during matches. A strong positive correlation was found between 3MT-derived Smax and the initiation of both HSR (r = 0.73, p < 0.01) and VHSR (r = 0.69, p < 0.05), highlighting the link between sprint capacity and match-specific high-intensity efforts. Lastly, a modified method for assessing player load demonstrated a high correlation with traditional methods (r = 0.99), while also accounting for individual metabolic demands. The modified approach offers a more nuanced understanding of player workload, potentially improving fatigue management, performance, and injury prevention. Conclusions The 3MT proved to be a valuable tool for evaluating individual physiological conditioning while also mapping on to key match performance metrics and external loads in university soccer players. The association with key performance indicators such as high-speed running capacity and sustained effort highlights its potential for optimizing training strategies.